The Relationship Of Pregnant Women's Knowledge And Attitudes Regarding Hypnobirthing At The Novi Lintas Timur Midwifery Clinic, Panyabungan District, Mandailing Natal Regency - Ferika Desi; Helmi Wardah Nasution (Sean Institute, 2023)
Hypnobirthing is a natural method used to eliminate fear, panic, tension and other pressures that haunt mothers during childbirth. Hypnobirthing is said to provide many benefits because it trains pregnant women to always relax, be calm and stabilize emotions. Hypnobirthing aims to enable mothers to give birth comfortably and relieve the pain of giving birth without the help of any anesthetic. The aim of this research is to identify the relationship between pregnant women's knowledge about hypnobirthing and pregnant women's attitudes towards hypnobirthing therapy in Novi midwives in 2023. This type of research uses an analytical survey method with a cross-sectional approach. The population in this study was the relationship between 60 pregnant women's knowledge about hypnobirthing at the Novi Midwife Clinic. Samples were taken by random sampling. The sample in this study was 37 pregnant women. Data collection uses a questionnaire. Data analysis uses univariate analysis and uses the chi square test. The research results showed that the majority of pregnant women's knowledge about hypnobirthing had sufficient knowledge as many as 19 people (51.4%) and the minority had good knowledge as many as 8 people (21.6%). Of the 19 respondents who had sufficient knowledge, the majority had a positive attitude about hypnobirthing, 16 people (43.2%), while of the 8 respondents who had good knowledge, the majority had a positive attitude, namely 8 people (21.6%). The results of the chi-square statistical test prove that there is a significant relationship between pregnant women's knowledge about hypnobirthing and pregnant women's attitudes towards hypnobirthing therapy, with a p value = 0.001 (p <0.05). The conclusion of the research is that there is a significant relationship between maternal knowledge about hypnobirthing and pregnant mothers' attitudes towards hypnobirthing therapy at the Novi Midwife Clinic in 2023